Let The Kierkegaardian Comedy Resume: Faith-Phobia And Faith-Ful Leaping In Evidence-Based Criteria For Therapeutic Care (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
This paper uses a Kierkegaardian framework to explore and critique current evidence-based, best practices protocol as an 'approximation process toward paradox reduction,' to use Kierkegaard's language, that does not attend to, fears, and yet, unwittingly enacts faithful leaping, or comporting without certainty, in discerning and engaging in effective therapeutic care.
Keywords: Existential; phenomenological; Kierkegaard; evidence; research; psychotherapy